Status and Threats to Mugger Crocodile Crocodylus palustris Lesson, 1831 at Rani Tal, Shuklaphanta Wildlife Reserve, Nepal - Bhatt, Harish P; Saund, Tej Bahadur; Thapa, Jham Bahadur (Nepal Journal of Science and Technology, 2013)
A study was carried out for preparing baseline information on water quality, population status and threats to Mugger crocodile, Crocodylus palustris Lesson at Rani Tal, Shuklaphanta Wildlife Reserve. Water quality analysis was conducted for three seasons (summer, autumn and winter) in the year 2008 - 2009. The study has found the physico-chemical contamination in the lake. The water quality parameters (dissolved oxygen, total hardness, free carbon dioxide, biological oxygen demand and ammonia) exceeded the normal range to support the Muggers. A survey around the lake recorded four adult Mugger crocodiles (>180 cm body length) basking in sandy and muddy bank during the investigation period. The lake is under pressure from diverse anthropogenic factors. The principal threats to the Mugger crocodile include water pollution, habitat destruction, sedimentation, food shortage, egg collection and seasonal fluctuation of water level. The total area and depth of the lake is diminishing due to encroachment by Phragmites karka and flash flood during monsoon. Conservation and proper management of the lake are urgently required. Nepal Journal of Science and Technology Vol. 13, No. 1 (2012) 125-131 DOI: http://dx.doi.org/10.3126/njst.v13i1.7451